PROGNOSTIC CRITERIA FOR THE COURSE OF SQUAMOUS CELL CARCINOMA OF THE LARYNX (A REVIEW OF LITERATURE) - N. A. Gorban; V. V. Popuchiev; V. V. Baryshev (Опухоли головы и шеи)
The review evaluates the use of the most common molecular biological markers to predict the course of squamous cell carcinoma of the larynx. It is proposed to use the markers Ki-67 and p53 as criteria and to take into account the specific features of the angioarchitectonics of a tumor.